2022
DOI: 10.1002/anie.202200905
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Influenced Fragmentations in Free‐Standing Three‐Dimensional Covalent Organic Framework Membranes for Hydrophobicity Switching

Abstract: The ordered open organic frameworks membranes are attractive candidates for flow‐assisted molecular separations. The physicochemical properties of such membranes mostly depend on their selectively chosen functional building blocks. In this work, we have introduced a novel concept of functional switchability of three‐dimensional covalent organic framework (3D‐COF) membranes through a simple solvent‐influenced fragmentation method. This room‐temperature interfacial synthesis provides free‐standing 3D‐COF membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Although the three-dimensional framework COF-300 was first reported in 2009, until now chemists had not succeeded in functionalizing COF-300 beyond the addition of −OH or −Br groups. Herein, we have shown that linkage transformation is a versatile way to functionalize COF-300 with alkyl, acetyl, or trifluoroacetyl groups. The resulting library of COF-300 derivatives led to the discovery of an outstanding PFAS adsorbent, COF-300-dimethyl, with a saturation capacity for perfluorooctanoic acid exceeding 250 mg/g.…”
Section: Discussionmentioning
confidence: 89%
“…Although the three-dimensional framework COF-300 was first reported in 2009, until now chemists had not succeeded in functionalizing COF-300 beyond the addition of −OH or −Br groups. Herein, we have shown that linkage transformation is a versatile way to functionalize COF-300 with alkyl, acetyl, or trifluoroacetyl groups. The resulting library of COF-300 derivatives led to the discovery of an outstanding PFAS adsorbent, COF-300-dimethyl, with a saturation capacity for perfluorooctanoic acid exceeding 250 mg/g.…”
Section: Discussionmentioning
confidence: 89%
“…The Brunauer–Emmett–Teller (BET) specific surface areas of COF1, COF2, and COF3 obtained through nitrogen sorption isotherms at 77 K are 1790±80, 1180±50, and 1400±30 m 2 g −1 , respectively (standard deviation based on triplicate measurements of the COF films obtained from multiple batches of fabrication), which are higher than many COF, and amorphous porous organic polymer (POP)‐based free‐standing films (Figure 2f, S7, Table S3) [48, 49] . The unimodal pore size distribution calculated through the quenched sphere density functional theory (QSDFT) method, [50, 51] also suggested the highly ordered nature of the COF films consisting of one‐dimensional nanochannels (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…reported the strategy of changing the interface of the two solvent to modulate the hydrophilicity/hydrophobicity of the resulting COFs membranes (Figure 8b). [ 90a ] The extent of the free functional groups in the imine‐ bonded (CN) covalent skeleton composed of tetrakis(4‐amino)phenylmethane (Tam) and 2, 5‐dibromoterephtahdehyde (Dbta) can be regulated by changing the interface of ethyl acetate/water or chloroform/water. Compared to the chloroform/water system (Tam Dbta‐2), the ethyl acetate/water system (Tam Dbta‐1) resulted in an increase in the amount of unreacted aldehyde functional groups (HCO) in the framework.…”
Section: Continuous Cofs Membranes Forms and Preparation Strategiesmentioning
confidence: 99%